Protecting children in the digital era : the use of alternative regulatory instruments - Lievens, Eva, 1979- (International studies in human rights, 2010)
From the mid-1990s onwards concerns regarding the exposure of children to harmful content in the increasingly digital media environment intensified. Soon thereafter policy makers across Europe realised that alternative regulatory instruments, such as self- and co-regulation, might be more appropriate than traditional legislation to address this matter of public interest. Taking the complex and delicate nature of protecting minors into account, this book provides an in-depth legal analysis of the alternative regulatory instruments that can be used to regulate content in the digital era, with pa.